Spreading of chemical substance after its accidental spillage onto the soil surface under unsaturated conditions and variable porosity (MCIT: Proceedings of International scientific and practical conference, 2019)
In this paper we study a mathematical model of soil moisture transport with variable porosity. The problem is set for the case of highly concentrated solute spilled onto soil surface. We investigate the way solute transfer, adsorption of contaminant by soil particles and variable porosity influence infiltration of solute into the soil profile. For that purpose, two models are used: a classical one and the one with consideration of mentioned factors. By comparing the results of both models, we established that high concentration of solute causes moisture transport to transpire more slowly, and the pollutant to remain on the soil surface for longer time. Numerical results indicate that porosity can vary considerably under the conditions of intensive contamination with salts.
Keywords: mathematical model; porous medium; moisture transfer; solute transport; finite elements method